Some Phase Transitions in Complex Structural Solids - Toʻrayev Ergash Yuldashevich; Ibragimova Rayhon Ahmedovna (International Journal on Integrated Education, 2021)
Copper atoms exist in two distinct charge states, according to a study of phase transitions observed in complex structural compounds of copper oxides using spectroscopic methods.